2012
DOI: 10.1111/j.1574-6941.2012.01441.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the microbiome and the metabolome of different regions of the equine hindgut

Abstract: The microbiome and associated metabolome of faecal samples were compared to those from the caecum and right dorsal colon of horses and ponies euthanised for nonresearch purposes by investigating the microbial population community structure as well as their functional metabolic products. Through the use of 16S rRNA gene dendrograms, the caecum microbiome was shown to cluster separately from the other gut regions. 16S rRNA gene‐based quantitative PCR (q‐PCR) also demonstrated differences between the caecum and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
125
2
11

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(159 citation statements)
references
References 70 publications
21
125
2
11
Order By: Relevance
“…The impact of the change of diet was marked, despite a high inter-horse variability as seen in the large mean standard errors that was found mainly in lactate concentrations in the caecum and colon. This confirmed the individual susceptibility, seen in horses fed high-starch diets as previously reported by several authors studying the equine hindgut microbial ecosystem (Julliand et al, 2001;Medina et al, 2002;Dougal et al, 2012 andSchoster et al, 2013;Sadet-Bourgeteau et al, 2014;Costa et al, 2015), and confirmed that some horses are more likely to develop digestive dysbiosis and potential intestinal diseases, such as colic. Using PCA the data showed that the two microbial ecosystems of horses clearly differed with the diet, and thus established that the hindgut microbiota was altered with the B diet.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The impact of the change of diet was marked, despite a high inter-horse variability as seen in the large mean standard errors that was found mainly in lactate concentrations in the caecum and colon. This confirmed the individual susceptibility, seen in horses fed high-starch diets as previously reported by several authors studying the equine hindgut microbial ecosystem (Julliand et al, 2001;Medina et al, 2002;Dougal et al, 2012 andSchoster et al, 2013;Sadet-Bourgeteau et al, 2014;Costa et al, 2015), and confirmed that some horses are more likely to develop digestive dysbiosis and potential intestinal diseases, such as colic. Using PCA the data showed that the two microbial ecosystems of horses clearly differed with the diet, and thus established that the hindgut microbiota was altered with the B diet.…”
Section: Discussionsupporting
confidence: 90%
“…These faecal parameters could be of particular usefulness for the diagnosis of microbial imbalances in the caecum and RV colon (the proximal hindgut). Previous studies have shown that faeces could be representative of the distal hindgut microbial composition, but not of the proximal hindgut (Da Veiga et al, 2005;Hastie et al, 2008;Dougal et al, 2012 andSchoster et al, 2013;Sadet-Bourgeteau et al, 2014;Costa et al, 2015). In this study the data demonstrated that variations in the proximal hindgut microbial ecosystem could have repercussions on the faecal one.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Indeed, it has yet to be demonstrated whether the faecal bacterial ecosystem is representative of that of the caecum and/or colon. Few studies have compared the bacterial community diversity of the equine caecum, colon and faeces (de Fombelle et al, 2003;Hastie et al, 2008;Dougal et al, 2011 and2012;Schoster et al, 2013). Of these few studies, all of them concluded that the faecal bacterial community was not representative of that of the caecum.…”
Section: Introductionmentioning
confidence: 99%
“…de Fombelle et al (2003) and Hastie et al (2008) quantified specific bacterial community in the right ventral v. left dorsal colon using culturing techniques and ventral v. dorsal colon using quantitative PCR. Recently, Dougal et al (2011 and2012) and Schoster et al (2013) assessed the impact of gut location at the level of bacterial community using terminal restriction fragment length polymorphism (TRFLP). Dougal et al (2011 and2012) found that the bacterial diversity of the right dorsal colon was similar to that of the faeces, which could be expected since, anatomically, the right dorsal colon is the closest to the rectum.…”
Section: Introductionmentioning
confidence: 99%